INTERCULTURAL COMMUNICATION: Theoretical Perspectives and Application - Nair, Kiran Ramachandran (Journal of Dharma, 1999)
The subject of intercultural communication has assumed contemporary significance in the present world of unprecedented movement and contact with increasing intercultural encounters among and across human communities. But its practice can be observed and traced back to periods of history in some countries when developments in communication and transportation technology were still rudimentary. History traditionally specifies four main cradles of civilization from which cultural influences have spread to several parts of the world. Moving from East to West, they are China, the Indian subcontinent, the ’Fertile Crescent’ and the Mediterranean, especially Greece and Italy. Of these four areas India deserves a larger share of credit than she is usually given because on a minimal assessment, she has deeply affected the religious life of most of Asia and has provided very important elements in the culture of the whole of South-East Asia as well as extending her influence, directly and indirectly to other parts of the world (Basham, 1979:1).